Mapping bathymetry and depositional facies on Great Bahama Bank. Issue 2 (1st November 2014) - Harris, Paul M. (Mitch); Purkis, Sam J.; Ellis, James; Swart, Peter K.; Reijmer, John J. G.
Abstract: Satellite imagery and an extensive set of water‐depth measurements have been used to map and critically evaluate the magnitude and patterns of bathymetry across Great Bahama Bank. Descriptions of previously collected sediment samples were combined with satellite imagery to map and refine the interpreted distribution of surficial carbonate sediments (depositional facies). Data reveal that 60% of Great Bahama Bank lies in 5 m or less of water. The deep portion occurs mainly in a generally east–west trending area in the southern portion of the platform. The re‐evaluation of the facies reveals that Great Bahama Bank is essentially a very grainy platform with muddier accumulations primarily in the lee of Andros Island. This area of Great Bahama Bank also experiences currents related to an excursion of the Florida Current onto the platform top; possibly enhancing sediment mud production through the generation of whitings. Sediment equivalents to mudstones, wackestones and mud‐rich packstones cover 8%, 5% and 14%, respectively, of the platform top, whereas sediment equivalents to mud‐poor packstones, grainstones and rudstones account for 20%, 45% and 3% of the surface area. Boundstones (reefs) were not specifically mapped in this study due to the resolution of the mapping. There is a poor relationship between the occurrence of the depositional texture and water depth, in that the grainier sediment types are abundant across the full range of water depths. The most abrupt lateral facies changes portrayed on the facies maps are observed leeward of islands, areas which also hold the highest diversity in facies type. The majority of the islands on the platform align with the north‐west/south‐east strike of the platform margin and these islands, in turn, exert control on the shape and orientation of facies belts that develop in proximity to them. For this reason, regions of the platform that contain principal islands host facies belts that align with the principal axis of the platform, whereas for regions lacking islands, the facies belts adopt an east–west trend consistent with prevailing winds and currents. There is a clear trend that the wide southern portion of the platform hosts the most continuous expanses of grain‐rich sediments.